WED Empowerment For Productive Age Orphanage Through Making Training Empek-Empek - Raden Hasan; Novfitri Landong Namora Sihombing Novfitri Sihombing (Ilomata International Journal of Social Science, 2020)
The purpose of this community service is to provide knowledge to the orphanage the importance of entrepreneurship, anything that can use as a business, how to make a product that will be manufacture and sold, as well as provide training and product marketing strategy generated. Educational entrepreneurship is a conscious effort to change a person's behavior. Educational activities are designed, organized, monitored, and evaluated to be able to achieve the goals set. Therefore, the implementation of education should give priority to dialogue and not as an object in this research conducted on orphans and orphans orphanage is located at Jl. Pajajaran Raya RT 003/005, Village Bencongan Beautiful, Housing III Karawaci. The method used in community service activities is to perform direct training and practice, in this training are given activities that include, presentation materials and practices make empek-empek culinary products presented by direct instructor skilled in the art. The implications of this community service activities are the need for product innovation and should think creatively to obtain products that are creative and innovative while remaining affordable and enjoyable.